Diagnosis and management of Non‐IgE gastrointestinal allergies in breastfed infants—An EAACI Position Paper. Issue 1 (27th August 2019) - Meyer, Rosan; Chebar Lozinsky, Adriana; Fleischer, David M.; Vieira, Mario C.; Du Toit, George; Vandenplas, Yvan; Dupont, Christophe; Knibb, Rebecca; Uysal, Piınar; Cavkaytar, Ozlem; Nowak‐Wegrzyn, Anna; Shah, Neil; et al.
Abstract: It is well‐established that food proteins, such as egg, soya, cow's milk and wheat, are detectable in breastmilk for many hours or days after ingestion. Exposure to these proteins is important to the process of developing tolerance but can also sometimes elicit IgE‐mediated and non–IgE‐mediated allergic symptoms in breastfed infants. Non–IgE‐mediated allergy, outside of food protein‐induced allergic proctocolitis and eosinophilic oesophagitis, is not well understood, leading to variations in the diagnosis and management thereof. A primary objective of the European Academy for Allergy and Clinical Immunology is to support breastfeeding in all infants, including those with food allergies. A Task Force was established, to explore the clinical spectrum of non–IgE‐mediated allergies, and part of its objectives was to establish diagnosis and management of non–IgE‐mediated allergies in breastfed infants. Eight questions were formulated using the Patient, Intervention, Comparison, Outcome (PICO) system and Scottish Intercollegiate Guideline Network (SIGN) criteria for data inclusion, and consensus was achieved on practice points through the Delphi method. This publication aims to provide a comprehensive overview on this topic with practice points for healthcare professionals.